Estimasi Cadangan Karbon Biomassa di Atas Permukaan pada Tegakan Mangrove Menggunakan Pengindraan Jauh di Tongke-Tongke, Sulawesi Selatan - Vina Nurul Husna (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2019)
Mangrove is one of the most intensive carbon sinks and plays a major role in the carbon cycle. However, the existence of mangrove is decreasing due to land use change that are not in accordance with its allocation, and disrupt the carbon cycle in the ecosystem. This study aims to estimate mangrove carbon stock using remote sensing technique in Tongke-tongke, South Sulawesi. Estimation using remote sensing usually has a low accuracy, therefore this research use multispectral (Landsat) and radar (PALSAR) sensor to increase the accuracy. Total carbon stocks in the study area based on model built for HH and HV polarization were 5662.85 ton and 6431.46 ton, respectively.